(untitled) (REVISTA NODO, 2019)
The protests against the excesses of tourism have been starring the newspapers’ covers around the world for several years. In Barcelona, a new neologism, turismofobia, seems to accompany –and qualify– the different manifestations that social unrest takes over some of its effects and main practices. Through a more than two-year ethnographic approach to the platform #EnsPlantem, Veïns en Perill d’Extinció, this article aims to show the role played by this type of movements around the application of neoliberal contemporary urban policies linked to touristification process that is living the city and also the neighborhood of Poblenou.